An Error Analysis on the Use of Preposition on Students’ Writing Descriptive Text - Hasrat Sozanolo Harefa; Roy Martin Laoli (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
Students with different first languages will make an error when learning a second language or foreign language. It occurs in spoken or written form. Based on the researcher’s observation and interview with the English teacher at SMK Negeri 1 Gunungsitoli Alo’oa, the researcher found some students’ problems in using preposition in writing descriptive text. The purpose of the research is to analyze the type of errors that is made by the tenth grade of Agriculture Department in SMK Negeri 1 Gunungsitoli Alo’oa in using the preposition in writing descriptive text.. The research used Corder’s theory of error classification namely, omission, addition, misformation, and misordering. As the result, the students made a 57.14% error on misformation, 26.53% on omission, 10.21% on addition, and 6.12% on misordering.